Mediasi dampak valuasi bisnis terhadap return saham perusahaan syariah yang terdaftar pada Jakarta Islamic Index 70 - Indriyani, Galuh; Rahman, Taufikur (Nur Science Institute, 2022)
This study aims to determine the effect of return on equity, earnings per share, and growth on sharia stock returns in the Jakarta Islamic Index 70 with firm value as the intervening variable—sampling with the purposive sampling technique. The sample used was 28 Sharia shares registered on JII70 for 2018–2020. The analytical tool used in this research is path analysis. The results of this study indicate that the variables return on equity and firm value affect stock returns in a positive and significant direction. The earnings per share variable have a significant adverse effect on stock returns. The growth was not significant on stock returns. Firm value does not mediate the effect of return-on-equity and earnings per share on stock returns, but firm value can mediate the effect of growth on stock returns.